PENGARUH DIFERENSIASI PRODUK, RATING CUSTOMER, DAN CONTENT MARKETING MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK ADEEVA GALLERY - Fisca Larasati (Jurnal Ilmu Administrasi Bisnis, 2025)
This research aims to determine product differentiation, customer ratings, and content marketing on purchasing decisions. This type of research is quantitative descriptive with research data obtained through questionnaires. The population in this study were Adeeva Gallery customers and the sampling technique used a probability sampling method with a sample size of 150 customers. Based on the results of the simultaneous test (F test), the value Fcount > Ftable is obtained, namely 30.496 > 3.057 with a significance value of 0.000 < 0.05 so it can be concluded that the product differentiation, customer rating and content marketing variables have an influence on purchasing decisions for Adeeva Gallery products at Shopee. Meanwhile, the results of the partial test (t test) show that the product quality obtained by the value of tcount > ttable is 3.717 > 1.976 with a significance value of 0.000 < 0.05 so it can be concluded that the product differentiation variable partially has a positive and significant effect on purchasing decisions for Adeeva Gallery products at Shopee , and the partial customer rating variable obtained from the tcount > ttable value, namely 2.609 > 1.976 with a significance value of 0.010 < 0.05 so it can be concluded that the partial customer rating variable has a significant effect on purchasing decisions for Adeeva Gallery products at Shopee. Meanwhile, the content marketing variable obtained a value of tcount < ttable, namely 3.594 < 1.976 with a significance value of 0.000 < 0.05, so it can be concluded that the content marketing variable partially has a significant effect on purchasing decisions for Adeeva Gallery products at Shopee. The ?2 value is 38.5%, while the remaining 61.5% is influenced by other factors not examined in this study. Keywords: Product Differentiation, Customer Ratings, Content Marketing, Adeeva Gallery